Ion-chromatographic determination of common anions in drinking water in some regions of the Republic of Armenia - Avetis Tsaturyan; Lusine Sahakyan; Lusine Hayrapetyan; Ela Minasyan; Ani Chakhoyan; Sergey Hayrapetyan; Ashot Saghyan (Pensoft Publishers, 2024)
The present study investigated the anion composition of drinking water from various cities and villages in Armenia, including spring water and tap water samples. The simultaneous separation was achieved for fluoride, chloride, bromide, nitrite, nitrate, sulfate, and phosphate anions with the correlation coefficients >0.998. Validation of the method was carried out in accordance with the requirements of guidelines in terms of selectivity, specificity, system suitability, linearity, accuracy, precision, lower limits of detection and quantitation, robustness, and stability. The method was suitable for routine drinking water quality assessment in line with the national or World Health Organization (WHO) regulations. The validated method was further used to analyze drinking water samples from different regions of Armenia. The observed concentrations for the anions in drinking water complied with the WHO limits for drinking water with some exceptions. The test method can be submitted to quality control laboratories as a convenient and practical tool for routine analysis and monitoring studies.